Company Reputation Mediates Sustainability Reporting on Investor Trust - Irwan Moridu; Nurcahya Hartaty Posumah (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study analyzes the effect of sustainability reporting on investor trust with corporate reputation as a mediating variable in manufacturing companies listed on the Indonesia Stock Exchange (IDX) during the period 2020–2024. The type of research used is quantitative with an explanatory research approach. Data was collected through annual reports and sustainability reports published by manufacturing companies listed on the IDX during that period. The data collection technique was carried out using the documentation method. Data analysis used the Structural Equation Modeling (SEM) approach based on Partial Least Squares (PLS) to test the relationship between variables and measure the mediation effect. The results of the study show that sustainability reporting has a positive and significant impact on corporate reputation and directly increases investor trust. Sustainability reporting significantly boosts investor trust, largely by building a corporate reputation. Credible and transparent reporting strengthens this indirect link. Therefore, effective sustainability reporting is crucial for enhancing both reputation and investor trust. Manufacturing companies should prioritize robust sustainability reporting and proactive reputation management within their investor relations.